The Effectiveness of Let’s Read Application to Improve Student’s Speaking Skill - Maulidiyah, Afita (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2025)
Media plays a significant role in enhancing students’ English language skills, and the development of digital media has provided new learning tools. One such tool, the Let’s Read application, offers accessible resources for improving speaking abilities. This study aims to assess the effect of the Let’s Read application on students' speaking proficiency. A quasi-experimental design was employed, involving an experimental group and a control group. The experimental group used digital media from the Let’s Read application, while the control group used printed stories from the same application. The study sample consisted of Grade 10 students, with classes 10.2 and 10.3, each containing 30 students. Data were collected through speaking assessments conducted as pre-tests and post-tests. Data analysis was performed using SPSS version 25. Inter-rater reliability was assessed with a t-test to check for score consistency between two raters, and hypothesis testing was conducted using the Mann-Whitney U test, due to non-normality and heterogeneity in the data. The results showed that the inter-rater reliability values (Sig. 2-tailed) were all above 0.05, indicating no significant differences between raters' scores, which confirms the data's reliability. Further analysis revealed that the experimental group significantly outperformed the control group, with a mean rank score of 36.72 compared to 24.28 for the control group. The Mann-Whitney U test yielded a significance value of 0.005, indicating that the Let’s Read application effectively improved students' speaking ability.